ANALISIS PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN PADA GURU PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR NEGERI MUNTOK - Santi Virgianti (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2016)
This study aimed to know the performance of PAI teachers in doing a planning, especially for making a lesson plan. That performance was evaluated from the document quality of lesson plan of Islamic education subject in state primary schools throughout the District of Muntok, West Bangka districts. Having known the quality of the lesson plan, then analyzed what the crucial thing that became the shortage of the lesson plan was. The type of research that was used was a descriptive research (analysis of documents) by qualitative approach. The research used population. Population of the research was all subject teachers of Islamic Education (PAI) which was registered as a teacher with the status of government employees in 18 state primary schools in the District of Muntok. Data analysis technique used was as a descriptive analysis. There were 10 aspects in this assessment: aspect of the completeness of lesson plan documents, aspect of suitability component of lesson plan, aspect of the formulation of indicators of achievement of competencies, aspect of formulation of learning objectives, feasibility aspects of learning objectives, aspects of the selection and organization of teaching materials, aspects of the selection of learning method, the feasibility aspects of learning objectives, aspects the selection of learning resources and feasibility aspects of assessment of learning outcomes. From the results of the research and discussion which was obtained in this research were expected that teacher of Islamic education in state primary schools of Muntok District, should make its own lesson plan and effort of making lesson plan should be enhanced.